If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X2+X2=56.25
We move all terms to the left:
X2+X2-(56.25)=0
We add all the numbers together, and all the variables
2X^2-56.25=0
a = 2; b = 0; c = -56.25;
Δ = b2-4ac
Δ = 02-4·2·(-56.25)
Δ = 450
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:X_{1}=\frac{-b-\sqrt{\Delta}}{2a}X_{2}=\frac{-b+\sqrt{\Delta}}{2a}
The end solution:
\sqrt{\Delta}=\sqrt{450}=\sqrt{225*2}=\sqrt{225}*\sqrt{2}=15\sqrt{2}X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-15\sqrt{2}}{2*2}=\frac{0-15\sqrt{2}}{4} =-\frac{15\sqrt{2}}{4}X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+15\sqrt{2}}{2*2}=\frac{0+15\sqrt{2}}{4} =\frac{15\sqrt{2}}{4}
| 4=b/30 | | (x/80)+(x/120)=0 | | 3x+4=6x–5= | | 4x/3-7=17 | | ⦁ 5x+7=4x+30 | | x2+18x-15=11x-10 | | 5(2p+7)=120 | | 965000/x=1.75 | | 06x=18 | | 9z+102=103 | | s6+20=188 | | 20+4b=1/3b+5.28 | | a/4-6=16 | | (x-2)/3=12 | | m^{2}+24m+63=0 | | -4x+1=-6x+10 | | b/3b=5(2-b)-4(1-3b)* | | 3x-8+x=4x-8 | | 4x-8+x=4x-8 | | 6t=42t= | | (x-3)/5+4=0,2x+6 | | 5x+17=11x-5 | | 6r+11=3r+2* | | 3x-2=12x-93 | | 2(n+1)=8n-1 | | 5x+36=12x+1 | | 4(6x–7)=144 | | 4(m+2)=6m-3 | | 3x-11=3x-1 | | 8x-37=3x-7 | | 3(x-5)=7+12 | | 2x−1=4x+2 |